Correlating Coefficient of Friction and Shear Force to Platen Motor Current in Tungsten and Interlayer Dielectric Chemical Mechanical Planarization at Steady-State Conditions. (13th April 2020) - Headley, R.; Frank, C.; Sampurno, Y.; Philipossian, A.
Abstract : Following up our earlier work that highlighted the relationship between shear force (SF) and platen motor current (PMC), in parallel with the relationship between coefficient of friction (COF) and PMC for various tungsten and interlayer dielectric (ILD) chemical mechanical planarization (CMP) cases at non-steady-state conditions, we explored whether or not PMC could be used as a reliable indicator instead of SF and COF at steady-state conditions. For the 12 cases studied, 72 distinct steps were analyzed. It was determined that PMC somewhat mirrored SF and PMC for long time (i.e. 10 s or longer) intervals after data averaging and applying a trend matching algorithm. SF and PMC trends matched only about 64% of the time (ranges between 45% to 85%) for all 72 steps, while PMC and COF trends matched 62% of the time ranging between 42% and 85%. PMC-SF and PMC-COF correlations were fairly poor at 1-sec time intervals as evidenced by much lower percent match values. Such poor correlations proved that at small time intervals, PMC was not sensitive enough to capture important information regarding myriad fluid dynamics and tribological phenomena and the instantaneous stick-slip occurrences encountered in CMP.